The raging sea the powerful account of the worst tsunami in U.S. history - Powers, Dennis M. (Citadel Press, 2005)
Uses historical research and personal accounts of survivors to tell the story of the tsunamis that hit Crescent City, California on Good Friday, 1964, which damaged hundreds of homes and businesses and killed eleven people. Includes some information about Alaska.